Doege-Potter syndrome associated to metastatic solitary fibrous tumor - Matheus de Oliveira Andrade; Matheus de Oliveira Andrade; Nathália da Cruz de Sousa; Paulo Siqueira do Amaral; Samantha Cabral Severino da Costa; Luiz Guilherme Cernaglia Aureliano de Lima; Delmar Muniz Lourenço Júnior; Olavo Feher (University of São Paulo, 2022)
Solitary fibrous tumor (SFT) is a rare fibroblastic mesenchymal neoplasm with an estimated annual incidence of 0.35 per 100,000 individuals. Doege-Potter syndrome is a paraneoplastic syndrome related to solitary fibrous tumor clinically characterized by hypoglycemia, occurring in less than 5% of cases. Herein, we report a case of metastatic SFT associated with recurrent severe hypoglycemia. A 43-year-old male with a noncontributory medical history presented with a painless and progressive growing mass in the right thigh. The histological evaluation rendered the diagnosis of SFT, and tumor resection was performed. One year after the operation, on the oncological follow-up, he was admitted to the emergency unit, manifesting an early-morning seizure associated with a severe hypoglycemia. The laboratory findings of non-islet cell tumor hypoglycemia (NICTH) in the background of a relapsed metastatic solitary fibrous tumor were consistent with the diagnosis of Doege-Potter syndrome. Hepatic embolization associated with oral glucocorticoid was an efficient palliative treatment to control the hypoglycemic crisis and allow hospital discharge.